TRAUMATIC L4 –L5 SPONDYLOLISTHESIS WITH VERTICAL SHEAR FRACTURE OF PELVIS: A CASE REPORT - DR. ANIL KUMAR. S. V,; DR. VINOD KUMAR MAKANNAVAR,; DR. SAMARTH ARYA,; DR. MANOHAR. P. V, (International Journal of Pharma and Bio Sciences, 2015)
We report a case of traumatic listhesis of L4 over L5 vertebra with vertical shear fracture of pelvis in a 45 year old male. The patient was treated surgically immediately after the injury. His radiological and operative ï¬ndings showed anterior listhesis of L4 over L5 vertebra with dislocation of bilateral facet joints at L3-L4 and L4-L5 level and fracture of spinous processes of L4-L5 vertebra with fracture of right lamina of L4 vertebra. There was also evidence of diastasis of pubic symphysis with displaced communited fracture of right iliac bone.Surgically he was treated by decompression and reduction, L3-L5 pedicular screw ï¬xationalong with L3 to L4 laminectomy, L3-L4 and L4-L5 discectomyandReconstruction plating for pubic diastasis and right iliac bone fracture.